2020
DOI: 10.1016/j.jebo.2020.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Conditional cooperation and the effect of punishment

Abstract: We study how punishment influences conditional cooperation. We ask two questions: 1) how does conditional cooperation change if a subject can be punished and 2) how does conditional cooperation change if a subject has the power to punish others. In particular, we disentangle the decision to be a conditional cooperator at all from the strength of conditional cooperation. We find that the possibility of being punished increases the strength of conditional cooperation. At the same time the possibility of being pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Our findings may enhance understanding of previous research on the use of punishment. Kirchkamp and Mill (2020) investigated how conditional cooperation changes when a participant can be punished or has the right to punish others. They found that the possibility of being punished increased the strength of conditional cooperation and the number of free riders, while the possibility of punishing others generally promoted cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may enhance understanding of previous research on the use of punishment. Kirchkamp and Mill (2020) investigated how conditional cooperation changes when a participant can be punished or has the right to punish others. They found that the possibility of being punished increased the strength of conditional cooperation and the number of free riders, while the possibility of punishing others generally promoted cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental research has shown that the threat of punishment can increase conditional cooperation (Fehr & Gachter, 2000 ; Lergetporer et al, 2014 ). However, punishment has also been shown to increase cheating, which might be due to defectors compensating for being punished by attempting to extract more from the public good (Kirchkamp & Mill, 2020 ). Players’ knowledge that cheaters can be punished can impact their behaviours.…”
Section: Discussionmentioning
confidence: 99%